The comparsion of teo different asophageal motility cathaters recording lower esophageal sphincter pressure - Serhat BOR; Oktay TEKEŞİN and Hakan YÜCEYAR and Nadir YÖNETÇİ and Hanefi ÇAVUŞOĞLU (Turkish Journal of Gastroenterology, 2019)
-